SURGICAL MANAGEMENT OF CUTANEOUS MELANOMA IN THE ERA OF COVID-19 PANDEMIC: A SINGLE CENTER EXPERIENCE - Mladenović, Stefan; Kovačević, Predrag; Višnjić, Aleksandar; Anđelković Apostolović, Marija (Acta medicae Medianae, 2023)
Timely started surgical treatment represents the gold standard in melanoma therapy and keeps mortality at a low level. The pandemic caused by SARS-CoV-2 has affected the availability of health care both nationally and globally. The aim of this study was to examine the impact of the COVID-19 pandemic on newly operated cutaneous melanoma in patients and to contribute to identifying the impact of the pandemic on the healthcare system in Serbia. We conducted a single institution retrospective study including patients who consecutively underwent surgery for cutaneous melanoma at the Clinic for Plastic and reconstructive Surgery, University Clinical center of Niš, between January 1, 2018 and March 15, 2023. We compared the pre-pandemic (01/Jan/18 - 14/Mar/20) and pandemic (15/Mar/20 - 15/Mar/23) periods by evaluating patient age, sex, body distribution, Breslow thickness, pT staging, mitotic index rate and ulceration status. No differences were observed between age (p = 0.666), sex (p = 0.720), body distribution (p = 0.109), Breslow thickness (p = 0.172), pT staging (p = 0.274), mitotic index rate (p = 0.257), and ulceration status (p = 0.787) in the two examined groups. Statistically significant differences were observed in the melanoma subtype (χ2 = 9.241; p = 0.026). Distribution of lentigo maligna in patients diagnosed with melanoma during the pandemic was statistically lower. To date, the diagnostic delay caused by COVID-19 has generally not led to unfavorable characteristics of the primary cutaneous melanoma. Follow-up studies are needed in the coming years to identify the potential impact on stage distribution and long-term survival.